Odpowiedzi

2009-09-28T00:49:21+02:00
A) 2 5/9 + 2 1/3 * 4 1/3 =2 5/9 + 7/3 *13/3 =2 5/9 + 91/9 =
2 5/9 + 10 1/9 =12 6/9=12 2/3

b) 5 1/7 * 1 4/9 - 6: 4 2/3=36/7 * 13/9 - 6: 14/3=4/7 * 13- 6*3/14=
52/7 - 18/14=104/14 - 18/14=86/14=6 1/7

c)
3 1/2 * (2 1/4 - 1 1/2 : 6)=7/2 * (2 1/4 - 3/2* 1/ 6)=
7/2 * (2 1/4 - 1/4)= 7/2 * (2 )= 7


d)
5 8/36 - 1 6/36
________ __________ =
11 /3 *(1 1/4 - 2/4)


4 2/36
________ ___ =
11 /3 *(3/4)


4 1/18
________ = 73/18: 11/4= 73/18 * 4/11= 73/9 *2/11= 146/99
11/4


1 5 1